Cooperation Performance of Nusa Cendana University in 2019-2023 - Melinda TALLAK; William DJANI; Ajis Salim Adang DJAHA (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the performance of cooperation of Nusa Cendana University in the last five years (2019–2023), and to identify factors that support and hinder the effectiveness of the implementation of the cooperation. The study used a qualitative approach with an instrumental case study method, and was conducted at Nusa Cendana University, Kupang. Informants were determined purposively from three faculties representing the categories of high (FKIP), medium (FST), and low (FISIP) cooperation performance. The results of the study show that in general, Nusa Cendana University has established various forms of cooperation at the university, faculty, and study program levels. However, there are disparities in the performance of cooperation between work units, as reflected in the number of cooperation documents and the level of implementation of cooperation agreements (MoU, MoA, IA). The most dominant cooperation is carried out in FKIP, while FISIP and postgraduate programs show relatively low achievements. Factors that influence cooperation performance include ability and motivation factors at the study program level. Supporting factors include: faculty leadership initiatives, availability of regulations and guidelines for cooperation, collaborative experience, and active partner networks. Inhibiting factors include the lack of an integrated coordination system, limited human resources, low administrative literacy, and no specific cooperation budget. The study recommends strengthening institutional systems, enhancing HR capacity at the study program level, and developing measurable follow-up strategies. Optimizing these aspects is expected to improve Nusa Cendana University's cooperation performance more effectively and sustainably.